Achieving and sustaining secured business operations : an executive's guide to planning and management - Ajmani, Neelesh (Apress, 2017)
Proactively plan and manage innovation in your business while keeping operations safe and secure. This book provides a framework and practices to help you safeguard customer information, prevent unauthorized access, and protect your brand and assets. Securing company operations is a board-level discussion. Across all industries, companies are pouring millions of dollars into taming cybercrime and other related security crime. Achieving and Sustaining Secured Business Operations presents a holistic approach looking top down, bottom up, and sideways. The end goal is to achieve and sustain a safe environment to conduct secured business operations while continuously innovating for competitive advantage.